Perlindungan Hukum Bagi Investor Terhadap Pelaku Usaha yang Melakukan Bisnis Online Secara Ilegal - Kadek Yudi Astrawan; Ni Luh Made Mahendrawati; Putu Ayu Sriasih Wesna (Jurnal Analogi Hukum, 2022)
The rapid advancement of information and communication technology has made it easier for some unscrupulous business actors to do online business illegally in cryptocurrency, cryptocurrency itself is a digital asset on the internet. The problem that can be raised is, how is the legal protection for investors against illegal online businesses? And what are the legal consequences for business actors who do illegal online business? This thesis uses a normative legal research method and uses a conceptual approach and legislation. After conducting research, it is known that cyber crime is difficult to overcome by the government which only relies on conventional positive law. There are two forms of legal protection for investors, namely, preventive and repressive legal protection. Based on the Consumer Protection Act, investors can file a class action lawsuit against business actors who conduct online business illegally, especially in the case of cryptocurrencies. The legal consequences for business actors who conduct online business illegally in cryptocurrencies are contained in Bappebti regulation 5/2019, precisely in Article 21 Paragraph 2.